+0  
 
0
146
1
avatar+2509 

Help.

NotSoSmart  Jan 3, 2018
 #1
avatar+87294 
+1

21.   Rearrange as

 

x^4 + 27x^2 - 324  =  0       factor as

 

(x^2  -  9)  ( x^2  + 36)  = 0

 

(x + 3) ( x - 3)  ( x + 6i) (x - 6i)  = 0

 

Set each factor to 0 and solve for x and we get the solutions  x = -3, 3, - 6i, 6i

 

 

22.  ( s +  3v)^5   =

 

s^5   +  5*s^4*(3v)  + 10*s^3*(3v)^2  +  10*s^2*(3v)^3  + 5*s*(3v)^4  + (3v)^5  =

 

s^5  + 15s^4v + 90s^3v^2  + 270s^2v^3 + 405sv^4  + 243v^5

 

 

cool cool cool

CPhill  Jan 3, 2018

12 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.